Enhancement of antibacterial activity in nanofillers incorporated PSF/PVP membranes. (11th April 2018) - Pramila, P; Gopalakrishnan, N
Abstract: An attempt has been made to investigate the nanofillers incorporated polysulfone (PSF) and polyvinylpyrrolidone (PVP) polymer membranes prepared by phase inversion method. Initially, the nanofillers, viz, Zinc Oxide (ZnO) nanoparticle, Graphene Oxide-Zinc Oxide (GO-ZnO) nanocomposite were synthesized and then directly incorporated into PSF/PVP blend during the preparation of membranes. The prepared membranes have been subjected to FE-SEM, AFM, BET, contact angle, tensile test and anti-bacterial studies. Significant membrane morphologies and nanoporous properties have been observed by FE-SEM and BET, respectively. It has been observed that hydrophilicity, mechanical strength and water permeability of the ZnO and GO-ZnO incorporated membranes were enhanced than bare membrane. Antibacterial activity was assessed by measuring the inhibition zones formed around the membrane by disc-diffusion method using Escherichia coli (gram-negative) as a model bacterium. Again, it has been observed that nanofillers incorporated membrane exhibits high antibacterial performance compared to bare membrane.